Serum and tissue levels of vitamin A and E gastric and esophageal cancer - M. Kürşat TÜRKDOĞAN; Haluk TESTERECİ; Tahir KAHRAMAN; İlyas TUNCER; Ekrem ALGÜN; İbrahim H. YÖRÜK (Turkish Journal of Gastroenterology, 2019)
-